Understanding solastalgia from a decolonised, Indigenist lens: a scoping review - Upward, Kisani; Usher, Kim; Saunders, Vicki; Maple, Myfanwy (Frontiers in Public Health, 2024)
In the context of this review, we as co-authors are mindful of and respect the tensions or politics associated with proclaiming, or discussing the identities of Australia's First Peoples. Therefore, in the context of this review, the often-preferred term Aboriginal refers to the traditional owners of Australia. Where possible, traditional place/tribe names are written to acknowledge the ownership and origins of the information referenced within this review. Furthermore, we wish to acknowledge the stories and traditional knowledges shared by the authors of the papers referenced within this review. These words of Country and Kin have contributed to the development and conceptualisation of this literature review and we wish to pay our respects and appreciation.